2013
DOI: 10.1002/ceat.201300460
|View full text |Cite
|
Sign up to set email alerts
|

Axial Equilibrium Distance and Positioning of Particles in a Laminar Tube Flow

Abstract: Particle transport in a laminar tube flow at low Reynolds numbers leads to accumulation of particles at specific equilibrium radii. The equilibrium radius depends on the particle size. Small particles find their equilibrium radius near the wall and large particles near the tube axis. During their radial migration to the equilibrium position, the particles move in axial direction with the flow. In an experimental setup, the axial equilibrium distance is measurement for several tube Reynolds numbers. The axial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Although a straight line through the data provides a good fit (R 2 = 0.97), the collective data suggests an inflection between 500 and 900 °C that might relate to char decomposition 8,50 and the secondary tar reactions. 12,52 Furthermore, these results are in good qualitative agreement with the yield of gas at different reactor temperatures for other biomass types reported in vastly different studies. 56−62 The MSMR experiments are inherently dynamic; i.e., events are always non-isothermal.…”
Section: Energy and Fuelssupporting
confidence: 84%
See 1 more Smart Citation
“…Although a straight line through the data provides a good fit (R 2 = 0.97), the collective data suggests an inflection between 500 and 900 °C that might relate to char decomposition 8,50 and the secondary tar reactions. 12,52 Furthermore, these results are in good qualitative agreement with the yield of gas at different reactor temperatures for other biomass types reported in vastly different studies. 56−62 The MSMR experiments are inherently dynamic; i.e., events are always non-isothermal.…”
Section: Energy and Fuelssupporting
confidence: 84%
“…Other studies also report a higher production of gas for microcrystalline cellulose as compared to that for whole biomass. …”
Section: Resultsmentioning
confidence: 95%
“…For individual spherical particles entrained by flowing laminar liquid through a tube, it was found that particles move into a streamline offcenter and dependent upon particle size. 35 In keeping with this finding, Newton's equation of motion was solved and the radial trajectory varied until the best fit was found between the predicted particle motion and experimentally determined motion on the basis of laser clocking.…”
Section: Experimental Methodsmentioning
confidence: 99%